Korelasi Kemampuan Menulis Pegon Dan Membaca Kitab Berbahasa Arab Jawi Santri Madrasah Diniyah Takmiliyah Awwaliyah Al-Hijrah Mojotengah - Nurul Khofifah; Muhammad Heri Prianto (Jurnal Pendidikan Agama Islam Miazhar, 2022)
The author conducted research on the correlation of the ability to write pegon and read books in Jawi Arabic at Madrasah Diniyah Takmiliyah Awwaliyah Al-Hijrah Mojotengah because here the observations show an interesting thing to study there, there is a lesson in the Jawi Arabic language, to be able to read and understand sentences. contained in it, it is very important to study pegon. Because there are still many students who can't read and write pegon. Whereas in Madrasah Diniyah it is very important to know pegon because it is used to read and interpret all kinds of forms of books. This study aims to determine the correlation between the ability to write pegon and read Arabic books in Jawi santri at Madrasah Diniyah Takmiliyah Awwaliyah Al-Hijrah Mojotengah. This type of research is quantitative with bivariate correlation techniques using Kendal Tau correlation statistics. This study used a non-probability sampling technique with the saturation method. The population in this study were all grade 3 and 4 students at Madrasah Diniyah Takmiliyah Awwaliyah Al-Hijrah Mojotengah. The results showed that a percentage of 67.45% was obtained from pegon's writing ability. Then a percentage of 81.41% was obtained from the ability to read Jawi Arabic books. Then, supported by the Kendal Tau correlation results, the correlation coefficient is 0.685 with a significance of 0.000, because the significance is <0.05, then Ho is rejected, meaning Ha is accepted. Based on the results of this study it can be stated that there is a significant relationship between the ability to write pegon and read Arabic books in Jawi students at Madrasah Diniyah Takmiliya Awwaliyah Al-Hijrah Mojotengah.